Neural Receptors Associated with Depression: A Systematic Review of the Past 10 Years - Câmara, Alice B.; Brandão, Igor Augusto (CNS & Neurological Disorders - Drug Targets, 2020)
Over the past few years, experimental research has been carried out to analyze the role of specific receptors in depression to better understand the mechanisms and pathophysiological aspects of the disease. In this paper, we aim to investigate the receptors family most involved in depression, as well as the tissues in which most depression related-receptors are expressed. The article also aims to identify the functions of the main receptors predominantly associated with the pathology. This review used a systematic methodology (Prospero; ID 168584) and followed the PRISMA guidelines. Studies were searched in PubMed/MEDLINE, Scientific Electronic Library Online, Web of Science, and Directory of Open Access Journals databases. Quantitative studies with conclusive results regarding receptors involved in depression were selected. The charts and network were made using R programming language and statistical analyses were carried out using SPSS v25 software. It can be seen that G protein-coupled receptors family is the most studied (p < 0.05). These receptors are expressed in the cerebral cortex, basal ganglia, and can interact with each other. A great number of studies have evaluated receptors related to beneficial effects in the disease (p < 0.05). The inflammation response and cell survival/proliferation are the main functions related to these receptors (p < 0.01) and behavioral tests in mice are the main methodologies applied in these studies (p < 0.05). Finally, the most influential protein on the network of receptors involved in depression is the Bradykinin receptor B1. G protein- coupled receptors located in cell membranes involving especially protective effects in depression and that expressed mainly in the cerebral cortex and basal ganglia have shown significant importance in this review. In addition, inflammation response or cell survival/proliferation are the main functions performed by the receptors related to depression as observed in this work.
Keywords: cell proliferation